Harnessing T Cells to Control Infections After Allogeneic Hematopoietic Stem Cell Transplantation - Basso, Sabrina; Compagno, Francesca; Zelini, Paola; Giorgiani, Giovanna; Boghen, Stella; Bergami, Elena; Bagnarino, Jessica; Siciliano, Mariangela; Del Fante, Claudia; Luppi, Mario; Zecca, Marco; Comoli, Patrizia (Frontiers in Immunology, 2020)
Dramatic progress in the outcome of allogeneic hematopoietic stem cell transplantation (allo-HSCT) from alternative sources in pediatric patients has been registered over the past decade, providing a chance to cure children and adolescents in need of a transplant. Despite these advances, transplant-related mortality due to infectious complications remains a major problem, principally reflecting the inability of the depressed host immune system to limit infection replication and dissemination. In addition, development of multiple infections, a common occurrence after high-risk allo-HSCT, has important implications for overall survival. Prophylactic and preemptive pharmacotherapy is limited by toxicity and, to some extent, by lack of efficacy in breakthrough infections. T-cell reconstitution is a key requirement for effective infection control after HSCT. Consequently, T-cell immunotherapeutic strategies to boost pathogen-specific immunity may complement or represent an alternative to drug treatments. Pioneering proof of principle studies demonstrated that the administration of donor-derived T cells directed to human herpesviruses, on the basis of viral DNA monitoring, could effectively restore specific immunity and confer protection against viral infections. Since then, the field has evolved with implementation of techniques able to hasten production, allow for selection of specific cell subsets, and target multiple pathogens. This review provides a brief overview of current cellular therapeutic strategies to prevent or treat pathogen-related complications after HSCT, research carried out to increase efficacy and safety, including T-cell production for treatment of infections in patients with virus-naïve donors, results from clinical trials, and future developments to widen adoptive T-cell therapy access in the HSCT setting.